Pengembangan Media Ajar Augmented Reality Card Simulasi Pengenalan Bangun Ruang Berbasis Assemblr Edu untuk Meningkatkan Minat dan Hasil Belajar Siswa - Sabila, Siti Zahra; Azmi, Nadya; Hadriana, Syalaisha Dwi; Aini, Putri Nur; Siregar, Sutan Surya Darpan; Siregar, Nurhasanah (Papanda, 2026)
This study aims to develop Augmented Reality (AR) learning media based on Assemblr Edu for the topic of flat-faced geometric shapes and to determine its feasibility, practicality, and impact on students' interest and learning outcomes. The research method used is Research and Development (R&D) with the 4D development model, which includes Define, Design, Develop, and Disseminate. The subjects of the study were eighth-grade students at SMP Swasta Cerdas Murni during the 2024/2025 academic year. Research instruments consisted of expert validation sheets, learning interest questionnaires, teacher response questionnaires, and learning outcome tests (pretest and posttest). The results of expert validation on the material obtained an average score of 84%, and media expert validation scored 95%, both categorized as